POLITIK DAKWAH DAN DAKWAH POLITIK DI ERA REFORMASI INDONESIA - Rosa, Andi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
This research activity parse dzikir majelis Susilo Bambang Yudhoyono (SBY) "Nurussalam" which has a strategic role in the democratic era. His status as a society organizations (NGOs) are positioned optimally by interest groups, political organizations and even into the container. By analyzing the dataobtained through interviews and documentation, the results of this study indicate that this council makes verses of the Qur’an that deals with the concept of al-‘ummah, al-ukhuwwah al-islamiyya, and al-ta'āwun as a cornerstone in interpreting paragraph integrative social which is then used as a propaganda entity. Proselytizing as mass communication, political communication line with more likely to use communication as a way to mobilize the masses massif. Even activities have been able to carry out the functions of political propaganda as part of the interest-group system.***Penelitian ini berusaha untuk mengurai kegiatan Majelis Dzikir Susilo Bambang Yudhoyono (SBY) “Nurussalam” yang memiliki peran strategis di era reformasi. Statusnya sebagai organisasi masyarakat (Ormas) diposisikan secara maksimal oleh kelompok kepentingan, bahkan menjadi wadah lembaga politik. Dengan mengganalisis data yang diperoleh melalui wawancara dan dokumentasi, hasil penelitian ini menunjukkan bahwa majelis ini menjadikan ayat al-Qur’an yang berkaitan dengan konsep al-‘ummah, al-ukhuwwah al-islāmiyyah, dan al-ta’āwun sebagai landasan dalam menafsirkan ayat sosial integratif yang kemudian dijadikan sebagai sebuah entitas dakwah. Dakwah sebagai komunikasi massa, sejalan dengan komunikasi politik yang lebih cenderung memanfaatkan komunikasi sebagai cara massif untuk menggalang massa. Bahkan kegiatannya telah mampu melaksanakan fungsi politik dakwah sebagai bagian dari sistem interest-group.